Recurrent Hyphema After Periocular Dog Bite in A 3-Year-Old: A Diagnostic Enigma - Subedi, Kumudini; Gautam, Maria; Pradhan, Sangita; Tiwari, Niva; Byanju, Raghunandan (Journal of College of Medical Sciences-Nepal, 2025)
Background Dog bites have been reported to cause destructive and avulsive ocular injuries. There have been rare instances of intraocular effect with an intact globe. Hyphema in such context must be dealt with a high degree of clinical suspicion. Case: A 3-year-old male was brought to the department with history of dog bite to the lateral aspect of left orbit following which his guardians noted persistent redness of the ipsilateral eye. Clinically, grade IV hyphema was noted which persisted even after anti-rabies prophylaxis was completed. Ultrasonography noted few vitreous opacities with no mass lesion. Hyphema was washed. Iris neovascularization with ectropion uveae was noted. Diffuse posterior segment abnormality was seen with no exact pathognomonic feature on table. The child returned with similar hyphema with clot in the anterior chamber with no other inciting factors 3 weeks later. Repeated imaging was misleading towards the exact diagnosis and the eyeball was enucleated whereby the histopathology established the exact diagnosis. Conclusion: A variety of clinical diagnosis must be kept in mind when a suspicious clinical scenario presents. The vision as well as the life of the patient may be at stake when sinister diagnoses are not kept in mind.